Firmographic analysis and the role of ICT in advancing green economy and sustainability in Tashkent - Kurbanova Maftuna; Samatov Nuriddin (BIO Web of Conferences)
Firmographic data and analyses demonstrate their usefulness, especially when integrated with Information Telecommunication Technologies (ICT), in optimizing state administration and local government functions. Companies and organizations with diverse characteristics have varying interests and challenges, making segmentation crucial for tailored strategies. For instance, a high-revenue entity is more likely to adopt advanced ICT solutions than a lower-revenue one. Firmographic segmentation is used to group entities into smaller, more targeted segments for effective strategy deployment. This method enhances the relevance of messages and solutions offered, increasing the likelihood of successful adoption and implementation. For example, targeting specific administrative needs with ICT tools tailored to their challenges fosters digitalization and superior e-governance practices. This approach underscores the critical role of ICT in promoting efficiency, supporting sustainability, and aligning operations with green economic goals. This paper examines how ICT facilitates firmographic segmentation, fosters green economic activities, and embeds sustainability into the mechanisms of government bodies in Tashkent. Key findings highlight ICT's role in enhancing operational efficiency and advancing eco-friendly governance strategies.